116 Canadian Community Paediatricians' Perspectives of Sport Medicine in Residency and in Practice. (29th October 2021) - Purcell, Laura; Campos, Sarah; Dickinson, Mike; Thompson, Graham
Abstract: Primary Subject area: Community Paediatrics Background: Participation by children and adolescents in organized sports and recreational sporting activities is increasingly popular in Canada. Although the health and psychosocial benefits of sports for children are significant, participation in sports confers an increased risk of injury, resulting in a considerable burden of visits to emergency departments and primary care offices. Despite the frequency of sport-related injuries, there are documented gaps in sport and exercise medicine (SEM) education in paediatric training, leading to many practicing paediatricians feeling uncomfortable in managing these issues. Objectives: We sought to describe Canadian community paediatricians' perspectives about SEM in training and practice. This descriptive, cross-sectional cohort study of practicing Canadian community paediatricians was designed to assess: i) self-reported practice profiles with respect to sport issues; ii) perceptions of SEM training during paediatric residency; and iii) comfort level with management of sport injuries. Design/Methods: To address these questions, a cross-sectional electronic survey of Canadian community paediatricians was conducted between February and March 2020. A survey was emailed to full members of the community paediatrics section of the Canadian Paediatric Society (CPS) (n=370) by CPS administrative staff. Participants were asked about musculoskeletal (MSK)/sport issues seen, how they manage these cases, their comfort level with diagnosis and management of sport injuries (on a 5-point Likert scale), and their perceptions of MSK/SEM training during paediatric residency. Results: The response rate was 23.0% (85/370). A quarter of respondents (20/85; 23.4%) reported seeing MSK/sport issues very often; a third (27/85; 31.7%) were comfortable managing these patients on their own. Almost all respondents did not feel that they had received adequate SEM training during paediatric residency (81/85; 95.3%). Respondents were most comfortable managing concussion, rating their comfort 4.17/5 on a 5-point scale (95% CI=3.96-4.38), and Osgood-Schlatter's disease 3.86/5 (95% CI=3.60-4.11). Participants were uncomfortable managing acromioclavicular joint separations 1.81/5 (95% CI=1.58-20.6) and elbow pain 2.65/5 (95% CI=2.40-2.90). Regression analysis indicated that only the frequency of MSK/sport-related visits was associated with provider comfort level (p < 0 .001). Conclusion: Most Canadian community paediatricians do not manage many patients with sport-related issues and are not comfortable managing these patients on their own. They feel that SEM training during their paediatric residency inadequately prepared them for practice. Incorporating more SEM training into paediatric residency programs may increase comfort level with MSK/sport issues and change referral patterns and practice patterns amongst community paediatricians.